The Research Progress in the Design and Development of Photocatalytic Materials - Chen Gaoyou (MATEC Web of Conferences, 2025)
The development of efficient photocatalytic materials is crucial to solving environmental problems and promoting sustainable energy development. This paper explores the application of photocatalytic materials in solving energy and environmental problems through empirical research, focusing on comparing the performance and scalability of different materials. Traditional TiO₂ photocatalysts are widely studied due to their high chemical stability, non-toxicity and low cost, but their wide band gap of about 3.2 eV can only utilize a very small part of ultraviolet light. Although metal oxides (such as ZnO, α-Fe₂O₃, WO₃) have the advantages of adjustable band gap and abundant resources, they generally face problems such as photocorrosion and low carrier mobility. Sulfides and nitrides (such as CdS, MoS₂, g-C₃N₄) are of interest due to their visible light absorption ability, but their stability and photocorrosion problems are prominent. Emerging materials such as perovskite oxides and metal-organic frameworks (MOFs) have significant potential in water oxidation and pollutant degradation. In general, although various materials have improved the efficiency of light energy utilization to varying degrees, band gap regulation, electron-hole pair recombination, durability and cost issues still restrict their practical application.